Budget And Extra-Budgetary Funds Of Budget Organizations - Mirzayev Ozod Furkatovich , (European Journal of Life Safety and Stability (2660-9630), 2022)
Funds of budget organizations from budgetary and extra-budgetary sources are the highest liquidity assets of organizations and are means of payment of liabilities. Targeted and efficient use of funds related to the implementation of activities is carried out on the basis of estimates made separately on the basis of budget classification for each source of funding. All the issues concerning budgetary and extra-budgetary sources of budget organizations are discussed in the article